Perampingan Birokrasi Antara Kemajuan Atau Kemauan Politik - Riyadi, Slamet (Sekolah Tinggi Ilmu Pemerintahan Abdi Negara, 2017)
Bureaucracy is an integral system in an operation but organizations that prioritize organizaional work bureaucracy become ineffective and inefficient. The government has discussed the need for downsizing in bureaucracy, downsizing is intended to make bureaucracy in organization more effective. But the discourse cannot be ralized and the goverment actually prolongs tge bureaucracy, for example by the appointment of represetatives of ministers. In the future this is a challenge in the administration of an efficient and effective goverment, so that seriousness of the goverment is treated even though the law already exists like Law number 5 of 2014 concerning bureaucratix reform, Invitation-law no 22 of 1999, no 32 of 2004 and Law No. 23 of 2004.